Thyroid Nodule Image Analysis using Morphological Segmentation - Mohan, Malathi; Srinivasan, Dr.S. (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
Computer-aided investigative processing has become an important part of medical practice. New growth of high expertise and use of a choice of imaging modalities, more confront arise so that high rate information can be produced for disease finding and behavior. Ultrasonography of Thyroid gland is the most common, portable, widely accessible, cheap, painless and secure.Â It is used to distinct the thyroid nodule images that are classified into two categories: (i) benign thyroid ample, (ii) malignant lump of thyroid gland. In this paper, Mathematical Morphology is used to segment the thyroid region and measure the area, perimeter, width and height of the thyroid area. Thyroid nodule images are taken from twenty peoples as samples. Keywordsâ€”Â Thyroid, Morphological operation, Ultrasound, Segmentation, Tumor